Analisis Penggunaan Afiksasi Bahasa Madura dalam Buku Paket Sekkar Anom 3 Bab 1 Kelas IX SMP/MTS - Nadila Devi Tsabita; Muhammad Amin Amirullah; Hanina Zahra Al Muhdlar; Hasan Suaedi (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Madurese, as one of the regional languages used by more than thirteen million speakers, has an important role in maintaining the ethnic and cultural identity of the Madurese people. This research aims to analyze the use of affixations in Madurese contained in the Sekar Anom 3 Package Book Chapter 1 for class IX SMP/MTS. Madurese, as a regional language with a complex morphological system, has various forms of affixation, including prefixes, infixes, suffixes and confixes. Using qualitative descriptive methods, this research identifies words that undergo the affixation process, analyzes their form, and reveals their morphological and semantic functions. The research results show that the affixation process not only enriches the structure and meaning of words in Madurese but also reflects its flexibility and uniqueness in word formation. Prefixes such as a-, è-, and ma- are used to provide causative, passive, or formal functions, while infixes such as -um- and -en- expand the meaning of the base word. The suffixes -a, -na, and -aghi as well as confixes such as ka-an, pa-an, and e-na are also found to strengthen descriptive, indicating, or command functions.